Integrated Magnetotelluric (MT), Gravity and Seismic Study of Lower Kutai Basin Configuration - Selvi Misnia Irawati; Hidayat Hidayat; Edy Wijanarko; Hendra Grandis (Journal of Engineering and Technological Sciences, 2022)
This work describes a subsurface basin configuration of the Lower Kutai Basin (hereinafter LKB) in East Kalimantan, Indonesia, as inferred from combination of magnetotelluric (MT), seismic, and gravity data. LKB is structurally controlled mainly by the Samarinda Anticlinorium extending in a NNE-SSW direction and is one of the most prolific hydrocarbon basins in Indonesia. The phase tensor analysis of MT data from most stations and frequencies exhibited a 2D character with a relatively low skew (-3° < β < 3°).  The geo-electrical strike direction was estimated at N30°E, which is in good agreement with the regional geological strike with a NNE-SSW direction. 2D MT inversion modeling was performed to infer the subsurface resistivity distribution associated with LKB’s configuration. From the integration of MT, seismic and gravity models it was shown that LKB’s configuration is composed mainly of sandstone, black shale, claystone, and basement rocks. The conductive zones of the MT models are associated with thermal alteration of black shale, which changes its mineralization, leading to lower resistivity. Hence, the black shale may be interpreted as potential hydrocarbon source rock in LKB.